2021
DOI: 10.3389/fcvm.2021.699492
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Natriuretic Peptides for All-Cause Mortality, Right Ventricular Failure, Major Adverse Events, and Myocardial Recovery in Advanced Heart Failure Patients Receiving a Left Ventricular Assist Device: A Systematic Review

Abstract: Aims: Major adverse event (MAE) rates during left ventricular assist device (LVAD) therapy in advanced heart failure (HF) patients are high, and impair quality of life and survival. Prediction and risk stratification of MAEs in order to improve patient selection and thereby outcome during LVAD therapy is therefore warranted. Circulating natriuretic peptides (NPs) are strong predictors of MAEs and mortality in chronic HF patients. However, whether NPs can identify patients who are at risk of MAEs and mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“… 25 In a systematic review, Janssen et al concluded that natriuretic peptides before LVAD implantation are not predictive of all‐cause mortality. 28 On the other hand, Bellavia et al showed that higher preoperative levels of NT‐proBNP were associated with a higher risk of post‐LVAD right heart failure.…”
Section: Discussionmentioning
confidence: 99%
“… 25 In a systematic review, Janssen et al concluded that natriuretic peptides before LVAD implantation are not predictive of all‐cause mortality. 28 On the other hand, Bellavia et al showed that higher preoperative levels of NT‐proBNP were associated with a higher risk of post‐LVAD right heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted February 8, 2023. ; https://doi.org/10.1101/2023.02.06.23285564 doi: medRxiv preprint LVAD implantation are not predictive of all-cause mortality. (27) On the other hand, Bellavia et al showed that higher pre-operative levels of NT-proBNP were associated with a higher risk of post-LVAD RHF.…”
Section: Discussionmentioning
confidence: 99%
“…(24) In a systematic review, Janssen et al concluded that natriuretic peptides before LVAD implantation are not predictive of all-cause mortality. (27) On the other hand, Bellavia et al showed that higher pre-operative levels of NT-proBNP were associated with a higher risk of post-LVAD RHF.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing interest in biomarkers as predictors of RVF. Elevated BNP reflects stretch of myocardial fibers and has been correlated with higher RVF rates ( 58 ). Increased osteopontin (>260 ng/ml) is a marker for greater extracellular matrix turnover and identifies patients with an ongoing profibrotic process that may potentially involve the RV, with increased risk of RVF ( 59 ).…”
Section: Pre-operative Prediction Of Right Ventricular Failurementioning
confidence: 99%